2012
DOI: 10.3389/fimmu.2012.00037
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Processing and Remodeling of the Endosomal Pathway: Requirements for Antigen Cross-Presentation

Abstract: Cross-presentation of endocytosed antigen as peptide/class I major histocompatibility complex complexes plays a central role in the elicitation of CD8+ T cell clones that mediate anti-viral and anti-tumor immune responses. While it has been clear that there are specific subsets of professional antigen presenting cells capable of antigen cross-presentation, identification of mechanisms involved is still ongoing. Especially amongst dendritic cells (DC), there are specialized subsets that are highly proficient at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 144 publications
(192 reference statements)
1
44
0
Order By: Relevance
“…31 In ovalbumin cross-presentation by mouse DC systems, data collectively suggests that processing may occur in either the endosomal or cytosolic/proteasomal pathway, depending on the endocytic route taken (ie, choice of binding to endocytic receptors) and configuration of the antigen (ie, soluble or particulate). 4,15,28,32,33 Our data in human MoDCs now shows that for HCMV pp65, Fc␥R-mediated uptake potentiates crosspresentation in a manner that requires processing both in the endosomal pathway and by the proteasome. Earlier flow cytometrybased work suggested that Fc␥R are not expressed on BDCA-3 ϩ DCs found in PBMCs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…31 In ovalbumin cross-presentation by mouse DC systems, data collectively suggests that processing may occur in either the endosomal or cytosolic/proteasomal pathway, depending on the endocytic route taken (ie, choice of binding to endocytic receptors) and configuration of the antigen (ie, soluble or particulate). 4,15,28,32,33 Our data in human MoDCs now shows that for HCMV pp65, Fc␥R-mediated uptake potentiates crosspresentation in a manner that requires processing both in the endosomal pathway and by the proteasome. Earlier flow cytometrybased work suggested that Fc␥R are not expressed on BDCA-3 ϩ DCs found in PBMCs.…”
Section: Discussionmentioning
confidence: 94%
“…Especially dendritic cells (DCs) are equipped with cell-biologic mechanisms supporting antigen processing and presentation, rendering them potent APCs. 4 In mice, DC subsets can be divided alongside their various specialties, including antigen uptake, processing and presentation to T cells, and migratory or resident properties in the body. [5][6][7] Mouse DCs expressing CD8␣ are specialized at antigen cross-presentation, the process by which exogenous antigen is presented as peptide/class I MHC complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The fast recycling route recycles cargo directly from early endosomes to the plasma membrane, whereas slow recycling occurs via a juxtanuclear-positioned endocytic recycling compartment (ERC) 2 (2). Nonrecycled cargo in early endosome transits into late endosomes (LEs) that eventually fuse with lysosomes where remaining cargo is degraded (3). Activation of CD4 ϩ and CD8 ϩ T cells requires presentation of peptide-MHC complexes of the appropriate specificity.…”
Section: Mouse Dendritic Cells (Dcsmentioning
confidence: 99%
“…1 Endocytic recycling compartment (ERC), a major perinuclear tubular network considered critical for slow endosomal recycling, has been suggested to be one route for crosspresentation. 2 This pathway is particularly relevant for soluble antigen presentation, as the former two routes are mostly used to describe particulate antigen processing, involving phagosomes. Here we report the unexpected finding that disruption of key regulatory factors of ERC, small GTPase proteins ARF6, Rab11a, and Rab22a, had no effect on soluble ovalbumin (OVA) crosspresentation in a model dendritic cell system.…”
Section: Cellular and Molecular Immunologymentioning
confidence: 99%